Peningkatan Keterampilan Independent Travel Melalui Prinsip Orientasi Mobilitas Pada Murid Tunanetra - Syamsuddin; Triyanto Pristiwawaluyo; Usman Fitri Srirahayu; Nur Fadhilah Umar (ILIN Institute Makassar, 2022)
The purpose of the study was to improve independent travel skills through the principle of mobility orientation for students with visual impairments in Elementary Class VI SLB Bulukumba. The research subject was 1 student with visual impairment in elementary grade VI SLB Negeri Bulukumba. The research method used is Single Subject Research with design A (Baseline 1) — B (Intervention) — A (Baseline 2). The data obtained were processed descriptively quantitatively. The results of this study indicate that there is an increase in independent travel skills with the principle of mobility orientation. based on the graph of independent travel skills on the subject, there is an upward/increasing trend (+). Thus, the results of this study suggest an increase in independent travel skills based on the principle of orientation for students with visual impairments in elementary grade VI SLB Negeri Bulukumba, South Sulawesi. Suggestions 1) In providing students with independent travel skills through the principle of mobility orientation, the following stages of the technique are carried out properly so that the results achieved are maximized. 2). For schools and orphanages, especially SLB Negeri Bulukumba, this independent travel skills training can be used as an alternative in improving mobility orientation abilities